2016
DOI: 10.1111/flan.12239
|View full text |Cite
|
Sign up to set email alerts
|

Saying vs. Doing: A Contradiction in the Professional Development of Foreign Language Teaching Assistants

Abstract: Despite the sizeable portion of foreign language (FL) instruction provided by graduate students now as teaching assistants (TAs) and in the future as faculty, few studies have considered TAs’ perspectives on their own professional development. To inform the professional development of FL graduate students as teachers, the present study updated and expanded on Brandl (2000) and Gonglewski and Penningroth (1998), who surveyed FL TAs about their perceptions of professional development opportunities. Using both qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Recent publications have underscored the need for expanding professional development opportunities for TAs. The call for higher involvement and collaboration among faculty members and TAs is recurrent, and the benefits of exposing TAs to the responsibilities they will face after graduation have been highlighted (Angus, ). This study assessed the effectiveness of pre‐ and in‐service training on TAs’ knowledge of and confidence in handling issues of accessibility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent publications have underscored the need for expanding professional development opportunities for TAs. The call for higher involvement and collaboration among faculty members and TAs is recurrent, and the benefits of exposing TAs to the responsibilities they will face after graduation have been highlighted (Angus, ). This study assessed the effectiveness of pre‐ and in‐service training on TAs’ knowledge of and confidence in handling issues of accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has discussed issues such as insufficient training opportunities, the inefficacy of existing training programs, TAs’ perceptions of their own unpreparedness to teach advanced or content classes, and TAs’ lack of readiness to face the broad range of challenges that will be posed as they enter their chosen profession. To this end, Angus () suggested that departments and TA mentors should emphasize the importance of raising TAs’ awareness regarding the challenges and expectations they will face. This implies a joint effort toward facilitating a holistic approach to training and mentoring as well as promoting the overarching understanding that the preparation of graduate students goes beyond enhancing the content that they learn in their own classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Without providing proper input it is not reasonable to expect good performance from them. Angus (2016) stresses in his research on the need of having trainings for the teaching assistants of teachers of second language. So that they can facilitate teachers fully and in this way students' performance and evaluation won't be disturbed.…”
Section: Formal Trainingmentioning
confidence: 99%